2003
DOI: 10.1007/s000110300000
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidative enzymes in human nasal mucosa after exposure to ozone. Possible role of GSTM1 deficiency

Abstract: Our findings suggest that GSTM1-deficiency has an impact on AOE-regulation after ozone exposure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 41 publications
0
17
0
Order By: Relevance
“…Cilenšek et al proposed a protective effect for the GSTM1-null genotype against retinopathy [46], explained by an up-regulation of other antioxidant enzymes, such as MnSOD [47]. On the contrary, the result of the aforementioned study is inconsistent with the study that showed a significant correlation between the GSTM1-null genotype and DR [38].…”
Section: Glutathione S-transferases (Gsts)mentioning
confidence: 93%
“…Cilenšek et al proposed a protective effect for the GSTM1-null genotype against retinopathy [46], explained by an up-regulation of other antioxidant enzymes, such as MnSOD [47]. On the contrary, the result of the aforementioned study is inconsistent with the study that showed a significant correlation between the GSTM1-null genotype and DR [38].…”
Section: Glutathione S-transferases (Gsts)mentioning
confidence: 93%
“…Therefore, SOD activity is calculated from the time-dependent difference between the MTT assay containing and not containing the homogenate. GPx was analysed using a modification of the coupled enzyme assay by Otto-Knapp et al (2003). GPx catalyses the oxidation of reduced glutathione (GSH, 0.1 mM) to oxidised glutathione (GSSG) accompanied with the reduction of H 2 O 2 (0.05%) to H 2 O.…”
Section: Methodsmentioning
confidence: 99%
“…The GPx activity was finally determined by following the oxidation of NADPH (0.15 mM) to NADP at 340 nm within the GR (1 U/ml) catalysed reduction of GSSG to GSH. GR was analysed according to Otto-Knapp et al (2003) by following the oxidation of NADPH (0.3 mM) to NADP at 340 nm within the GR catalysed reduction of GSSG (2 mM) to GSH.…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, SOD activity is calculated from the time-dependent difference between the MTT assay containing and not containing the homogenate. GPx was analysed using a modification of the coupled enzyme assay by Otto-Knapp et al (2003). Within the test, GPx catalysed the H 2 O 2 (0.05%)-dependent oxidation of reduced (glutathione, GSH; 0.1 mM) to oxidised glutathione (GSSG).…”
Section: Animals and Sample Collectionsmentioning
confidence: 99%
“…The GPx activity was finally determined by following the oxidation of NADPH (0.15 mM) to NADP at 340 nm within the GR (1 U/ml) catalysed reduction of GSSG to GSH. GR was analysed according to Otto-Knapp et al (2003) by following the oxidation of NADPH (0.3 mM) to NADP at 340 nm within the GR-catalysed reduction of GSSG (2 mM) to GSH.Thiobarbituric acid-reactive substances (TBARS). The concentration of TBARS was determined according to Du et al (2002).…”
mentioning
confidence: 99%